The Influence of Bugis Women’s Education on the Amount of Panai A Social and Cultural Study: A Case Study of the Bugis Community in Kateman District - Rohani, Siti (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
The uang panai’ tradition is one of the customary practices in Bugis marriage ceremonies, involving the giving of a sum of money from the groom’s family to the bride’s family. This money is used as wedding expenses in preparation for the marriage ceremony. The tradition symbolizes respect and honor toward women. This study examines the influence of Bugis women’s educational level on the amount of uang panai’ within the Bugis community in Kateman District, Riau, where the majority of residents are not ethnically Bugis. The research employs a qualitative ethnographic approach and uses the theory of acculturation as an analytical framework. The findings reveal that the higher the woman’s educational attainment, the greater the amount of uang panai’ requested by her family as a form of social appreciation. However, in a non-Bugis dominant environment, this practice has undergone adaptation through interfamily negotiations. Consequently, the uang panai’ amount among Bugis women in Kateman District differs from that in Bugis communities in Sulawesi. Acculturation plays a key role in maintaining the continuity of the tradition while allowing flexibility in its practice. [Tradisi uang panai’ merupakan salah satu tradisi yang ada dalam perkawinan masyarakat Bugis, yaitu berupa pemberian sejumlah uang dari pihak laki-laki kepada pihak perempuan, yang dipergunakan sebagai uang belanja untuk mempersiapkan acara perkawinan. Tradisi ini mempunyai arti sebagai bentuk sebuah penghargaan dan penghormatan kepada pihak perempuan. Penelitian ini membahas pengaruh pendidikan perempuan Bugis terhadap nominal uang panai’, dalam tradisi masyarakat Bugis di Kecamatan Kateman, Riau, yang mayoritas bukan bersuku Bugis. Penelitian menggunakan pendekatan kualitatif etnografi, dan menggunakan teori  Akulturasi sebagai pisau analisis. Hasil penelitian menunjukkan bahwa, semakin tinggi pendidikan perempuan, semakin besar nominal uang panai’ yang diminta keluarga sebagai bentuk penghargaan sosial. Namun, dalam lingkungan yang bukan mayoritas Bugis ini, ternyata mengalami penyusuaian melalui negosiasi antar keluarga. Sehingga nominal uang panai’ perempuan Bugis di Kecamatan Kateman, memiliki perbedaan besaran nominal, jika dibandingkan dengan masyarakat Bugis yang ada di Sulawesi. Akulturasi berperan dalam menjaga bagaimana tradisi tetap dijalankan sekaligus menungkinkan fleksibilitas dalam praktiknya.]